2023
DOI: 10.3390/electronics12061418
|View full text |Cite
|
Sign up to set email alerts
|

Model Predictive Control Based Energy Management Strategy of Series Hybrid Electric Vehicles Considering Driving Pattern Recognition

Abstract: This paper proposes an energy management strategy for a series hybrid electric vehicle based on driving pattern recognition, driving condition prediction, and model predictive control to improve the fuel consumption while maintain the state of charge of the battery. To further improve the computational efficiency, the discretization and linearization of the model is conducted, and the MPC problem is transferred into a quadratic programming problem, which can be solved by the interior point method effectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…MPC-based energy management strategy for hybrid electric vehicles, considering factors such as driver demand, traffic conditions, and energy availability was developed. The study demonstrated improved fuel economy and emissions reduction compared to traditional control strategies [23]- [26].…”
Section: Introductionmentioning
confidence: 90%
“…MPC-based energy management strategy for hybrid electric vehicles, considering factors such as driver demand, traffic conditions, and energy availability was developed. The study demonstrated improved fuel economy and emissions reduction compared to traditional control strategies [23]- [26].…”
Section: Introductionmentioning
confidence: 90%
“…It has the advantages of strong robustness, good control effect and high stability and has been widely used in linear and nonlinear control systems. Hao et al [30] optimized the predictive model, combining driving intention recognition and driving condition prediction with MPC, with the goal of improving fuel consumption while maintaining the SOC of the battery. To further improve the calculation efficiency, the model was discretized and linearized, and the MPC problem was transformed into a quadratic programming problem, which can be effectively solved using the interior point method.…”
Section: Introductionmentioning
confidence: 99%
“…Rule-based strategies are the most widely used and relatively mature due to their simple design, convenient implementation, and excellent real-time performance [10,11]. Ruan et al developed a rule-based shifting schedule and power split strategy for a dual-motor powertrain.…”
Section: Introductionmentioning
confidence: 99%